PENGARUH KOMPETENSI KERJA, DISIPLIN KERJA, KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Tiolina Fernanda Ujung; Agita Karina Br Ginting; Shindu Bayrewi; Rafida Khairani (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
Competence is a person's ability to do a job where that person excels in that job. Work discipline is a person's work abiAlity which reflects a great sense of responsibility to comply with the rules that exist in the company. Job satisfaction is a form of attitude from employees regarding feedback that they get from workers in the company where they work. Performance is the result of tasks that have been completed by employees in accordance with the standards and criteria given by the superior. In this case, job competence, work discipline, and job satisfaction are independent variables, while employee performance is the dependent variable. PT Danamas Insan Kreasi Andalan is a subsidiary of the BCA pension fund. Danamas Insan Kreasi Andalan is engaged in the credit card marketing business. PT Danamas Insan Kreasi Andalan provides marketing services, sales services, customer service and human resource development for an exclusive client, namely Bank Central Asia (BCA). The research method uses a quantitative approach, the type of research is descriptive quantitative. Data collection was carried out by interview, questionnaire and documentation study. Data analysis using multiple linear regression. The population in this study were all company employees, amounting to 100 people. The sample is determined by the formula used is a saturated sample where the total population is equal to the number of samples, namely 100 employees. sample and to test the validity taken 30 respondents outside the sample. The results showed that training, discipline and research are simultaneously and partially competence, discipline and satisfaction have a significant effect on the performance of the employees of PT. Danamas